Best Candlesticks Pattern to Trade Stocks - Cohen, Gil (International Journal of Economics and Financial Issues, 2020)
This research examines whether candlesticks patterns can predict trends swings. Our results indicate that well known two days "Engulfing" pattern have failed to produce a positive gain while the "Harami" pattern has barely succeeded to do so. A more complex patterns known as the "Kicker" barley achieved a positive average gain and was also outperform by the simple B&H strategy. We found that the "Stairs" pattern developed here, has achieved a positive gain for all twenty examined stock and has outperformed the B&H strategy for sixteen out of the twenty stocks. Keywords: Candlesticks Patterns, Trends, Algorithmic Trading, Stocks Investing. JEL Classifications: C1, M2 DOI: https://doi.org/10.32479/ijefi.9298